الامتحان الموحد للغة العربية لغير الناطقين بها - البيشاوي, محمد (Mayada: al-Multaqa al-Ilmy al-Alamy lil-Dirasat al-Arabiyah; Vol 1 No 1 (2023): مجموعة البحوث - الملتقى العلمي العالمي للدراسات العربية, 2024)
Tests are one of the most diverse and important assessment tools, and in fact they may be the most widespread. Tests help us understand the learner’s needs, behavior and thinking. In this research, the researcher follows the following two approaches: First: the descriptive approach, which will be used to describe the research problem represented by the lack of a standardized test for non-Arabic speaking students. This approach will be used to describe the problem accurately and in detail, and to identify its various dimensions and causes. Second: The analytical approach, which the researcher will use to dismantle the problem, analyze it in depth, find appropriate solutions, and develop the most important results and recommendations to achieve the research goal. The research reached several results, including: 1- Using a standardized test for the Arabic language leads to improving consistency and balance in assessing students’ level in the Arabic language, which can help improve the quality of education provided to non-Arabic speaking students, and can lead to improving their self-confidence and level in the Arabic language, and enhances the use of the test. Unifying the Arabic language, cultural integration and diversity in society. 2- Using a standardized test for the Arabic language helps in developing effective educational programs for non-Arabic speaking students, thus improving the quality of education provided to them. 3- Determining the levels of Arabic for non-native speakers and developing a standardized test for each level requires a careful analysis of the basic language skills that must be learned at each level, which can be measured through performance on tests. تُعتبر الامتحانات واحدة من أدوات التقييم المتنوعة والمهمة، وفي الواقع قد تُعتبر الأكثر انتشارًا. اذ تساعدنا الامتحانات في فهم احتياجات المتعلم وسلوكه وتفكيره. يتبع الباحث في هذا البحث المنهجين الآتيين: أولاً: المنهج الوصفي، والذي سيتم استخدامه لوصف مشكلة البحث المتمثلة في عدم وجود اختبار موحد للطلاب غير الناطقين باللغة العربية. وسيتم استخدام هذا المنهج لوصف المشكلة بشكل دقيق ومفصل، وتحديد أبعادها المختلفة وأسبابها. ثانياً: المنهج التحليلي، الذي سيستخدمه الباحث لتفكيك المشكلة وتحليلها بعمق، وإيجاد الحلول المناسبة ووضع أهم النتائج والتوصيات لتحقيق هدف البحث. حيث توصل البحث الى عدة نتائج نذكر منها:1- استخدام اختبار موحد للغة العربية يؤدي إلى تحسين الاتساق والتوازن في تقييم مستوى الطلاب في اللغة العربية، مما يمكن أن يساعد في تحسين جودة التعليم المقدم للطلاب الغير ناطقين باللغة العربية، ويمكن أن يؤدي إلى تحسين ثقتهم بأنفسهم ومستواهم في اللغة العربية، ويعزز استخدام اختبار موحد للغة العربية التكامل والتنوع الثقافي في المجتمع. 2- يساعد استخدام اختبار موحد للغة العربية في تطوير برامج تعليمية فعالة للطلاب الغير ناطقين باللغة العربية، وبالتالي تحسين جودة التعليم المقدم لهم. 3- يتطلب تحديد مستويات اللغة العربية لغير الناطقين بها وتطوير اختبار موحد لكل مستوى عملية تحليل دقيق للمهارات اللغوية الأساسية التي يجب تعلمها في كل مستوى، والتي يمكن قياسها من خلال الأداء في الاختبارات.